A New Language Policy for Indonesia - Eko Saputra; Andri Saputra (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
Indonesia is the house of multicultural ethnic groups with more than 700 individual vernacular languages. This diversity puts Indonesia into both strategic and a vulnerable condition. It is strategic because the culture-rich Indonesia can commodify the diversity for the benefits of the people, however, it is also vulnerable as it can pose serious threats to the existence of the nation. For several decades, Indonesia has given attention to the language policy. Yet, the implementation still needs appropriate modification for the improvement. Objective of the paper: This paper is written on the purpose of giving a new form of language policy to be implemented in Indonesia. Theoretical Framework: A scheme of language policy is proposed for educational setting in Indonesia. Justification: Some arguments are also provided to provide a strong justification for the necessity of implementation of the policy. Conclusion: 1. It is imperative to have a language policy that can promote unity and prevent any potential separatism, provide a sense of belonging to the nations and ethnic culture in terms of nationalism, and open access to knowledge enhancement and the global world. 2. It is also important to have qualified and committing teachers to the implementation of language policy. If both points are present, the benefits of language policy can obviously be obtained.